2021
DOI: 10.1002/mar.21537
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the jungle: A bibliometric analysis of research into construal level theory

Abstract: Construal level theory (CLT) offers a valuable framework to explain the mechanisms that trigger evaluations, predictions, and behaviors by linking the degree of mental abstraction (the construal level) to psychological distance. CLT‐related research has produced numerous publications in a variety of domains, impeding an ongoing overview of the research field and limiting its advancement. Addressing this concern, our paper presents the results of a comprehensive bibliometric analysis of CLT‐related research. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 112 publications
0
33
0
Order By: Relevance
“…Changes in distances perceptions also influence prediction, evaluation, and action (Adler & Sarstedt, 2021). The theory has advanced several aspects of consumer research on perception, information processing, preference shifts, and decision making.…”
Section: Construal Level Theorymentioning
confidence: 99%
“…Changes in distances perceptions also influence prediction, evaluation, and action (Adler & Sarstedt, 2021). The theory has advanced several aspects of consumer research on perception, information processing, preference shifts, and decision making.…”
Section: Construal Level Theorymentioning
confidence: 99%
“…Motivating this study, extant research has demonstrated that a wide range of consumption behaviors are informed by individuals' construal‐level (see Adler & Sarstedt, 2021 for recent overview). For instance, construing objects abstractly has been shown to lead individuals to assign greater importance to products placed in an online shopping cart and a subsequent reduction in the likelihood of shopping cart abandonment (Rubin et al, 2020).…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Motivating this study, extant research has demonstrated that a wide range of consumption behaviors are informed by individuals' construal-level (see Adler & Sarstedt, 2021 for recent overview).…”
Section: Construal and Consumption Behaviorsmentioning
confidence: 99%
“…Finally , a comprehensive and systematic review of conversational commerce is arguably best undertaken and published by Psychology & Marketing because (1) conversational commerce is a marketing phenomenon that reflects the deployment of conversational agents for value creation and service delivery in the marketplace, and in the process of doing so, influences customer behavior, which can be explained by the psychological process involving a myriad of perception and evaluation influencing factors, (2) the journal is home to psychological studies of marketing phenomenon, (3) the journal has explicitly called for papers in this area (Mariani & Perez‐Vega, 2020; Pentina & Bailey, 2022), and (4) the journal has a prolific and recent track record of publishing comprehensive and systematic reviews (Hassan et al, 2022; Mariani et al, 2022), including those relying on a bibliometric methodology (Adler & Sarstedt, 2021; Donthu et al, 2021a; Khan et al, 2020), with a review on conversational commerce or conversational agents virtually nonexistent.…”
Section: Introductionmentioning
confidence: 99%